The effect of perceived university support, entrepreneurial self-efficacy and proactive personality in promoting student entrepreneurial intention in Indonesia - Lestari, Elissa Dwi; Rizkalla, Nosica; Purnamaningsih, Purnamaningsih (Journal of Management and Business Education, 2022)
Entrepreneurship plays a pivotal role in economic growth for Indonesia. Unfortunately, the number of entrepreneurs in Indonesia is still lagging behind other ASEAN countries. The emergence of knowledge-based entrepreneurship makes universities become one of the vital supply sources for creating entrepreneurs. Even though it has institutional support from the Indonesian government, entrepreneurship is still not considered a promising alternative career choice. Therefore, this study aims to analyze the effect of university institutional support (perceived educational support, concept development support, and concept development support) and personal traits variables (self-efficacy and proactive personality) on Indonesian students' entrepreneurial intention. This study was conducted using a judgmental sampling technique on 302 active university students in Indonesia who have received entrepreneurship education. Data analysis in this study was carried out using the PLS-SEM. The findings of this study indicate that perceived educational support directly affects entrepreneurial intention. While, perceived concept development support and perceived business development support positively shape self-efficacy, leading to entrepreneurial intention. This study also confirms self-efficacy and proactive personality as predictors of entrepreneurial intention. Furthermore, the study also shows that self-efficacy mediates the relationship between proactive personality and Indonesian students' intentions to be entrepreneurs.